Method for preparing all-solid waste autoclaved brick by using dry desulfurization ash and all-solid waste autoclaved brick

By stirring and forming dry desulfurization ash with fly ash, furnace slag, and water slag, all solid waste autoclaved bricks are prepared, solving the problem of pollution in the accumulation of dry desulfurization ash, and achieving efficient resource utilization and strength improvement.

CN119591351APending Publication Date: 2025-03-11BEIJING YUZHI ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411482340.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively utilize dry desulfurization ash, which causes its storage to pollute the environment and fails to fully utilize its resource utilization potential.

Method used

Dry desulfurization ash is used as an exciter, stirred with fly ash, slag, and water slag, and then molded under high pressure and maintained in steam to prepare a fully solid waste autoclaved brick.

Benefits of technology

Through dry desulfurization ash, fly ash activity is stimulated, C-S-H gel and AFt crystals are generated, the strength and durability of autoclaved bricks are improved, and efficient resource utilization of industrial solid waste is achieved, environmental protection pressure is reduced and economic benefits are brought.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591351A_ABST
    Figure CN119591351A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing an all-solid-waste autoclaved brick by using dry desulfurization ash and the all-solid-waste autoclaved brick, and belongs to the technical field of recycling of desulfurization ash, the method comprises the following steps: taking dry desulfurization ash as an exciting agent, stirring with fly ash, furnace slag and water granulated slag, and adding 11-15% of water in the stirring process to obtain a mixture; carrying out compression molding on the mixture under the pressure of 10-15 MPa to obtain a green brick; and curing the green brick in steam at 180 DEG C for 10 hours to obtain a finished product of the all-solid waste autoclaved brick. Compared with autoclaved bricks prepared from semi-dry desulfurized fly ash, the autoclaved brick prepared from the semi-dry desulfurized fly ash has the advantages that the solid waste resource utilization rate is more outstanding, the early strength and durability are more excellent, corrosion caused by catalyst residues to production equipment is avoided, cement and other bonding reinforcing agents do not need to be added, and resource utilization of all solid wastes is truly achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of recycling of desulfurization ash, and in particular to a method for preparing all-solid waste autoclaved bricks by utilizing dry desulfurization ash and the all-solid waste autoclaved bricks. Background Art

[0002] During the production process, enterprises such as steel, coking, and coal-fired power plants will produce a large amount of flue gas containing sulfur dioxide. Due to the advantages of dry desulfurization technology such as small footprint, energy saving, and environmental protection, the above-mentioned enterprises gradually use dry desulfurization technology for flue gas desulfurization. Therefore, a large amount of desulfurization ash is produced every year. According to incomplete statistics, my country's steel and coking enterprises produce about 20 million tons of desulfurization ash every year. These desulfurization ashes are complex in composition and there are few resource utilization technologies. At present, most of them are stored, which causes great pollution to the environment. Therefore, how to make full use of desulfurization ash, turn it into treasure, and reduce its pollution to the environment is a problem that needs to be solved urgently.

[0003] To this end, the invention patent with publication number CN 103708808 B provides an autoclaved brick of sintered flue gas semi-dry desulfurization ash and a preparation method thereof. The method first catalytically oxidizes the sintered flue gas semi-dry desulfurization ash, and then stirs the sintered flue gas desulfurization ash with water according to the mass ratio of 30-47% slag, 15-25% fly ash, 20% crushed stone or river sand, 3-6% cement, 3% polyvinyl alcohol and 5-20% sintered flue gas desulfurization ash, extrudes it on a molding device and sends it to an autoclave for steaming to obtain an autoclaved brick. The patent uses low-temperature catalytic oxidation to pretreat the semi-dry desulfurization ash, and converts the calcium sulfite in the semi-dry desulfurization ash into calcium sulfate. In the process of treatment, the semi-dry desulfurization ash and the catalyst will agglomerate during the mixing and stirring process, and the oxidation efficiency is often not high. Usually, there is still a lot of calcium sulfite that has not been oxidized. At the same time, the residual catalyst will also affect the production equipment and finished products. Unoxidized calcium sulfite has the disadvantages of slow setting, slow coagulation and hardening, and volume expansion. Not only does it make the autoclaved bricks very low in strength at the initial stage of forming and prone to chipping and falling edges, it usually needs to be used with cement to ensure the initial strength. In addition, the unoxidized calcium sulfite gradually reacts slowly with the oxygen in the air over time to generate calcium sulfate, which gradually expands in volume, causing expansion and cracking damage to the autoclaved bricks over time. Summary of the invention

[0004] The present invention aims to provide a method for preparing all-solid waste autoclaved bricks using dry desulfurization ash and all-solid waste autoclaved bricks, in order to at least partially solve at least one of the above technical problems.

[0005] In order to solve the above technical problems, the first aspect of the present invention provides a method for preparing all-solid waste autoclaved bricks using dry desulfurization ash, comprising:

[0006] Using dry desulfurization ash as an activator, stirring it with fly ash, slag and water slag, and adding 11% to 15% of water during the stirring process to obtain a mixture;

[0007] Pressing the mixture under a pressure of 10 to 15 MPa to obtain a brick;

[0008] The brick blanks are cured in steam at 180° C. for 10 hours to obtain finished all-solid waste autoclaved bricks.

[0009] According to a preferred embodiment of the present invention, the mass proportions of the components in the mixture are: dry desulfurization ash: 10% to 30%, fly ash: 50% to 70%, slag: 10% to 25%, and water slag: 10% to 25%.

[0010] According to a preferred embodiment of the present invention, the dry desulfurization ash is a fine powder solid waste discharged after the calcium-based desulfurizer absorbs SO2 in the flue gas in the dry desulfurization process, with a specific surface area of ​​10 to 30 m 2 / g.

[0011] According to a preferred embodiment of the present invention, the mass proportions of the components in the dry desulfurization ash are: Ca(OH)2: 20% to 65%, CaSO4: 20% to 40%, and CaCO3: 10% to 25%.

[0012] According to a preferred embodiment of the present invention, the mass proportions of the main oxide components of the fly ash are: SiO2: 45% to 60%, Al2O3: 20% to 35%, Fe2O3: 5% to 10%, and CaO: 1% to 5%.

[0013] According to a preferred embodiment of the present invention, the slag is a melt generated in the metallurgical process and floating on the surface of liquid substances such as metals. The waste slag collected from the bottom of the boiler combustion chamber is crushed into granules. The slag particle size is 1mm to 3mm, and the bulk density is not more than 800kg / m 3 ;

[0014] The slag contains SiO2, Al2O3, Fe2O3, CaO and a small amount of sulfide.

[0015] According to a preferred embodiment of the present invention, the slag is solid waste discharged from a molten blast furnace slag produced by a steel enterprise during ironmaking and rapidly cooled in water.

[0016] According to a preferred embodiment of the present invention, the oxide components in the slag include: CaO, SiO2, Al2O3, MgO, CaS, MnS; the slag particle size is 1mm to 10mm, and the bulk density is about 1350 to 1600kg / m 3 .

[0017] In order to solve the above technical problems, the second aspect of the present invention provides an all-solid waste autoclaved brick, which is prepared by any of the methods described above.

[0018] According to a preferred embodiment of the present invention, the mass percentage of each component in the all-solid waste autoclaved brick is: dry desulfurization ash: 10% to 30%, fly ash: 50% to 70%, slag: 10% to 25%, and water slag: 10% to 25%.

[0019] In summary, the present invention utilizes calcium hydroxide and calcium sulfate in dry desulfurization ash to stimulate the activity of fly ash, so that the active silicon dioxide and active aluminum oxide glass in the fly ash are depolymerized, releasing potential activity, and reacting to form CS(A)-H gel, which is the source of strength of autoclaved bricks. At the same time, due to the presence of calcium sulfate in dry desulfurization ash, the reaction can form a small amount of AFt needle-shaped crystals, which fill the gaps in the CS(A)-H gel to form a network structure. AFt crystals are expansive. On the one hand, they can make the structure of autoclaved bricks more compact and increase the strength. On the other hand, they can effectively inhibit the shrinkage of the brick body and increase the durability of the autoclaved bricks. Compared with autoclaved bricks prepared using semi-dry desulfurization ash, the present invention is more prominent in the resource utilization rate of solid waste, and has better early strength and durability. There is no corrosion to the production equipment caused by the residual catalyst, and there is no need to add cement and other bonding enhancers, so that all solid waste can be truly utilized as resources. Compared with the prior art, the present invention has at least the following beneficial effects:

[0020] (1) The present invention utilizes all industrial solid waste in terms of raw material selection, and adopts pressing molding and autoclaving curing in the production process. Compared with ordinary clay red bricks, the present invention does not require high-temperature calcination, truly realizing energy conservation and emission reduction and turning waste into treasure.

[0021] (2) The present invention uses dry desulfurization ash as an activator, and utilizes calcium hydroxide and calcium sulfate and other components in the dry desulfurization ash to activate the activity of fly ash. Since the active SiO2 and active Al2O3 in the fly ash are both in the form of glass, they do not have the characteristics of hydration reaction under normal conditions. With the addition of dry desulfurization ash, due to the presence of calcium hydroxide, the liquid phase pH increases, the glass in the fly ash depolymerizes, the Si-O and Al-O bonds break, the fly ash activity is released, and the hydration reaction produces CSH gel. At the same time, the calcium sulfate introduced by the dry desulfurization ash can react with the active Al2O3 under alkaline conditions to obtain AFt crystals, forming a dense network structure, thereby improving the strength and durability of the brick body.

[0022] (3) The raw material slag used in the present invention is a melt generated during the metallurgical process and floating on the surface of liquid materials such as metals. It is mainly composed of silicon dioxide, aluminum oxide, calcium oxide, and magnesium oxide, and is discharged from the bottom of the boiler. On the one hand, due to the presence of metal oxides such as calcium oxide and magnesium oxide, the slag is alkaline, providing an alkaline environment for autoclaved brick materials, further stimulating the activity of fly ash and increasing the strength of autoclaved bricks; on the other hand, a small amount of fine powder particles in the slag can react with alkaline substances such as calcium hydroxide and water to generate a small amount of CSH gel, a compound with gelling properties, which increases the strength of autoclaved bricks.

[0023] (4) The raw material slag used in the present invention is in block or large granular form, which is crushed into particles of about 1 mm to 3 mm by a crusher and continuously assembled with desulfurization ash, slag and other materials, thereby greatly reducing the internal porosity of the autoclaved brick after pressing and forming, increasing the density of the brick body, and improving the strength and durability of the autoclaved brick.

[0024] (5) The bulk density of the raw material slag used in the present invention is less than 800 kg / m3. According to the difference in bulk density between slag and water slag, autoclaved bricks of different weights can be obtained by adding different ratios to meet the market demand for autoclaved bricks of different weights.

[0025] (6) The present invention fully utilizes industrial solid waste, realizes the resource utilization of industrial solid waste such as desulfurization ash, fly ash, slag, and water slag, reduces the environmental pressure of steel, coking and other enterprises, and can also bring economic benefits to the enterprises. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic flow chart of a method for preparing all-solid waste autoclaved bricks using dry desulfurization ash provided by an embodiment of the present invention. DETAILED DESCRIPTION

[0027] The features and exemplary embodiments of various aspects of the present invention will be described in detail below. In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with the accompanying drawings and Examples. It should be understood that the specific embodiments described herein are only configured to explain the present invention and are not configured to limit the present invention. For those skilled in the art, the present invention can be implemented without the need for some of these specific details. The following description of the embodiments is only to provide a better understanding of the present invention by illustrating examples of the present invention.

[0028] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the statement "include..." do not exclude the presence of other identical elements in the process, method, article or device including the elements.

[0029] The present invention provides a method for preparing all-solid waste autoclaved bricks using dry desulfurization ash, such as Figure 1 As shown, the method includes:

[0030] S1. Using dry desulfurization ash as an activator, stirring it with fly ash, slag and water slag, and adding 11% to 15% water during the stirring process to obtain a mixture;

[0031] In this embodiment, the mass proportions of the components in the mixture are: dry desulfurization ash: 10% to 30%, fly ash: 50% to 70%, slag: 10% to 25%, and water slag: 10% to 25%.

[0032] The dry desulfurization ash is a fine powder solid waste discharged after the calcium-based desulfurizer (mainly calcium hydroxide) absorbs SO2 in the flue gas in the dry desulfurization process, with a specific surface area of ​​10 to 30 m 2 / g. Preferably, the mass proportions of the components in the dry desulfurization ash are: Ca(OH)2: 20% to 65%, CaSO4: 20% to 40%, and CaCO3: 10% to 25%.

[0033] The fly ash is solid waste collected from the flue gas after coal combustion in coal-fired power plants. The mass proportions of the main oxide components in the fly ash are: SiO2: 45% to 60%, Al2O3: 20% to 35%, Fe2O3: 5% to 10%, CaO: 1% to 5%. The fly ash is in the form of fine powder, and the residue on the 45μm square hole sieve is not less than 45%.

[0034] The slag is a melt floating on the surface of liquid materials such as metals generated during the metallurgical process, and is the waste slag collected from the bottom of the boiler combustion chamber. It contains: SiO2, Al2O3, Fe2O3, CaO and a small amount of sulfide. After crushing, it is in the form of fine particles. The slag particle size is 1mm to 3mm, and the bulk density is not more than 800kg / m 3 .

[0035] The slag is the solid waste discharged from the molten blast furnace slag produced by the steel enterprises during ironmaking, which is placed in water and rapidly cooled. The oxide components in the slag include: CaO, SiO2, Al2O3, MgO, CaS, MnS; the particle size of the slag is 1mm to 10mm, and the bulk density is about 1350 to 1600kg / m 3 .

[0036] Exemplarily, in this step, the desulfurized ash, fly ash, slag and water slag can be measured in a certain mass ratio and then placed in a forced mixer for mixing and stirring for 2 minutes. Subsequently, a certain amount of water is added during the mixing process to control the moisture content of the mixture to 11% to 15%, and stirring is continued for 2 minutes to obtain a mixture.

[0037] Furthermore, in this step, the mass ratio of the slag and the water slag can be adjusted according to the difference in bulk density between the slag and the water slag, so that autoclaved bricks of different weights can be produced.

[0038] In other embodiments, the dry desulfurization ash may be replaced by a mixture of various materials having a composition close to that of the dry desulfurization ash, such as carbide slag and desulfurization gypsum.

[0039] In addition, materials such as steel slag and machine-made sand particles may be used to replace the water slag.

[0040] S2, pressing the mixture under a pressure of 10-15 MPa to obtain a brick;

[0041] Specifically, the mixture prepared in step S1 can be placed in a mold and pressed at a pressure of 10 to 15 MPa to obtain a green brick.

[0042] S3, curing the brick blank under steam at 180° C. for 10 hours to obtain a finished all-solid waste autoclaved brick.

[0043] The following is a detailed description of the method for preparing all-solid waste autoclaved bricks using dry desulfurization ash provided by the present invention through specific examples and comparison columns. The raw materials in each example and comparison column are: dry desulfurization ash is waste generated by desulfurization of coke oven flue gas, with a bulk density of 0.54kg / m 3 The fly ash is the third-grade fly ash produced by a power plant in Shanxi Province, and the 45μm square hole sieve residue is 38%; the slag is the waste slag collected from the bottom of the boiler combustion chamber after coal burning in a power plant in Shanxi Province, with a particle size of less than 2mm and a bulk density of about 764kg / m 3 The slag is water-quenched slag produced by ironmaking in a steel plant in Shanxi Province. The particle size is less than 10 mm and the bulk density is about 1520 kg / m 3 .

[0044] Example 1

[0045] A method for preparing all-solid waste autoclaved bricks using dry desulfurization ash, comprising:

[0046] Weigh the raw materials according to the mass proportion: 10% dry desulfurization ash, 66% fly ash, 15% slag, and 9% slag, add the raw materials with the said mass proportion into a mixer and dry mix for 2 minutes to mix evenly; then add mixing water to control the moisture content of the mixture at 13%±2%, and continue stirring for 2 minutes until the materials are evenly mixed to obtain a mixture.

[0047] The mixed material is placed in an autoclaved brick mold with a size of 530 mm*115 mm*24 mm, and pressed under a pressure of 10-15 MPa to obtain a brick blank;

[0048] The obtained bricks were cured in steam at 180°C for 10 hours to obtain finished autoclaved bricks. The compressive strength of the finished autoclaved bricks was tested.

[0049] Comparative Example 1

[0050] A method for preparing an autoclaved brick in this comparative example comprises:

[0051] Weigh the raw materials according to the mass proportion: semi-dry desulfurization ash 10%, fly ash 66%, slag 15%, slag 9%; add the raw materials with the mass proportion into the mixer and dry mix for 2 minutes to mix evenly; then add mixing water, control the moisture content of the mixture at 13% ± 2%, and continue to stir for 2 minutes until the materials are evenly mixed;

[0052] The uniformly mixed materials are placed in an autoclaved brick mold with a size of 530 mm*115 mm*24 mm, and pressed under a pressure of 10-15 MPa to obtain a brick blank;

[0053] The obtained bricks were cured in steam at 180°C for 10 hours to obtain finished autoclaved bricks. The compressive strength of the finished autoclaved bricks was tested.

[0054] Example 2

[0055] A method for preparing all-solid waste autoclaved bricks using dry desulfurization ash, comprising:

[0056] Weigh the raw materials according to the mass proportion: 15% dry desulfurization ash, 60% fly ash, and 25% slag; add the raw materials with the mass proportion into a mixer and dry mix for 2 minutes to mix evenly; then add mixing water, control the moisture content of the mixture to 13%±2%, and continue to stir for 2 minutes until the raw materials are evenly mixed to obtain a mixture;

[0057] The mixed material is placed in an autoclaved brick mold with a size of 530 mm*115 mm*24 mm, and pressed under a pressure of 10-15 MPa to obtain a brick blank;

[0058] The obtained bricks were cured in steam at 180°C for 10 hours to obtain finished autoclaved bricks. The compressive strength of the finished autoclaved bricks was tested.

[0059] Comparative Example 2

[0060] A method for preparing an autoclaved brick in this comparative example comprises:

[0061] Weigh the raw materials according to the mass ratio: 15% quicklime, 60% fly ash, and 25% slag; add the raw materials with the mass ratio into a mixer and dry mix for 2 minutes to mix evenly; then add mixing water, control the moisture content of the mixture to 13% ± 2%, and continue to stir for 2 minutes until the materials are evenly mixed;

[0062] The uniformly mixed materials are placed in an autoclaved brick mold with a size of 530 mm*115 mm*24 mm, and pressed under a pressure of 10-15 MPa to obtain a brick blank;

[0063] The obtained bricks were cured in steam at 180°C for 10 hours to obtain finished autoclaved bricks. The compressive strength of the finished autoclaved bricks was tested.

[0064] Example 3

[0065] A method for preparing all-solid waste autoclaved bricks using dry desulfurization ash, comprising:

[0066] Weigh the raw materials according to the mass proportion: 15% dry desulfurization ash, 60% fly ash, and 25% water slag; add the raw materials with the mass proportion into a mixer and dry mix for 2 minutes to mix evenly; then add mixing water, control the moisture content of the mixture to 13%±2%, and continue to stir for 2 minutes until the materials are evenly mixed;

[0067] The uniformly mixed materials are placed in an autoclaved brick mold with a size of 530 mm*115 mm*24 mm, and pressed under a pressure of 10-15 MPa to obtain a brick blank;

[0068] The obtained bricks were cured in steam at 180°C for 10 hours to obtain finished autoclaved bricks. The compressive strength of the finished autoclaved bricks was tested.

[0069] Comparative Example 3

[0070] A method for preparing an autoclaved brick in this comparative example comprises:

[0071] Weigh the raw materials according to the mass proportion: 5% quicklime, 10% semi-dry desulfurization ash, 60% fly ash, and 25% slag; add the raw materials with the mass proportion into a mixer and dry mix for 2 minutes to mix evenly; then add mixing water, control the moisture content of the mixture to 13%±2%, and continue to stir for 2 minutes until the materials are evenly mixed;

[0072] The uniformly mixed materials are placed in an autoclaved brick mold with a size of 530 mm*115 mm*24 mm, and pressed under a pressure of 10-15 MPa to obtain a brick blank;

[0073] The obtained bricks were cured in steam at 180°C for 10 hours to obtain finished autoclaved bricks. The compressive strength of the finished autoclaved bricks was tested.

[0074] The performance of the autoclaved bricks prepared in the above Examples 1 to 3 and Comparative Examples 1 to 3 was tested, and the results are shown in Table 1.

[0075] Compressive strength / MPa <![CDATA[Unit weight / (kg / m 3 )]]> Appearance Example 1 19.4 1.34 intact Comparative Example 1 10.7 1.41 Drop Corner Example 2 14.3 1.16 intact Comparative Example 2 11.8 1.22 Slight corner drop Example 3 18.5 1.57 intact Comparative Example 3 12.7 1.61 intact

[0076] Table 1 Autoclaved brick test results

[0077] It can be clearly seen from Table 1 that when the proportions of other components and processes are the same, the present invention uses dry desulfurization ash as an activator to effectively improve the compressive strength of the brick body and reduce the bulk density of the brick body.

[0078] Based on the above-mentioned method for preparing all-solid waste autoclaved bricks using dry desulfurization ash, the present invention also provides an all-solid waste autoclaved brick, which is prepared by any of the methods described above; the mass percentage of each component in the all-solid waste autoclaved brick is: dry desulfurization ash: 10% to 30%, fly ash: 50% to 70%, slag: 10% to 25%, and water slag: 10% to 25%.

[0079] In summary, compared with the prior art, the method for preparing all-solid waste autoclaved bricks using dry desulfurization ash and the all-solid waste autoclaved bricks provided by the present invention have at least the following beneficial effects:

[0080] (1) The present invention utilizes all industrial solid waste in terms of raw material selection, and adopts pressing molding and autoclaving curing in the production process. Compared with ordinary clay red bricks, the present invention does not require high-temperature calcination, truly realizing energy conservation and emission reduction and turning waste into treasure.

[0081] (2) The present invention uses dry desulfurization ash as an activator, and utilizes calcium hydroxide and calcium sulfate and other components in the dry desulfurization ash to activate the activity of fly ash. Since the active SiO2 and active Al2O3 in the fly ash are both in the form of glass, they do not have the characteristics of hydration reaction under normal conditions. With the addition of dry desulfurization ash, due to the presence of calcium hydroxide, the liquid phase pH increases, the glass in the fly ash depolymerizes, the Si-O and Al-O bonds break, the fly ash activity is released, and the hydration reaction produces CSH gel. At the same time, the calcium sulfate introduced by the dry desulfurization ash can react with the active Al2O3 under alkaline conditions to obtain AFt crystals, forming a dense network structure, thereby improving the strength and durability of the brick body.

[0082] (3) The raw material slag used in the present invention is a melt generated during the metallurgical process and floating on the surface of liquid materials such as metals. It is mainly composed of silicon dioxide, aluminum oxide, calcium oxide, and magnesium oxide, and is discharged from the bottom of the boiler. On the one hand, due to the presence of metal oxides such as calcium oxide and magnesium oxide, the slag is alkaline, providing an alkaline environment for autoclaved brick materials, further stimulating the activity of fly ash and increasing the strength of autoclaved bricks; on the other hand, a small amount of fine powder particles in the slag can react with alkaline substances such as calcium hydroxide and water to generate a small amount of CSH gel, a compound with gelling properties, which increases the strength of autoclaved bricks.

[0083] (4) The raw material slag used in the present invention is in block or large granular form, which is crushed into particles of about 1 mm to 3 mm by a crusher and continuously assembled with desulfurization ash, slag and other materials, thereby greatly reducing the internal porosity of the autoclaved brick after pressing and forming, increasing the density of the brick body, and improving the strength and durability of the autoclaved brick.

[0084] (5) The bulk density of the raw material slag used in the present invention is less than 800 kg / m 3 According to the difference in bulk density between slag and water slag, autoclaved bricks of different weights can be obtained by adding different ratios to meet the market demand for autoclaved bricks of different weights.

[0085] (6) The present invention fully utilizes industrial solid waste, realizes the resource utilization of industrial solid waste such as desulfurization ash, fly ash, slag, and water slag, reduces the environmental pressure of steel, coking and other enterprises, and can also bring economic benefits to the enterprises.

[0086] It should be clear that the present invention is not limited to the specific structures and processes described above and shown in the figures. For the sake of simplicity, a detailed description of the known methods is omitted here. In the above embodiments, several specific steps are described and shown as examples. However, the method process of the present invention is not limited to the specific steps described and shown, and those skilled in the art can make various changes, modifications and additions, or change the order between the steps after understanding the spirit of the present invention.

[0087] It should also be noted that the exemplary embodiments mentioned in the present invention describe some methods or systems based on a series of steps or devices. However, the present invention is not limited to the order of the above steps, that is, the steps can be performed in the order mentioned in the embodiments, or in a different order from the embodiments, or several steps can be performed simultaneously.

[0088] The above is only a specific implementation of the present invention. Those skilled in the art can clearly understand that for the convenience and simplicity of description, the specific working process of the system, module and unit described above can refer to the corresponding process in the aforementioned method embodiment, and will not be repeated here. It should be understood that the protection scope of the present invention is not limited to this. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be covered within the protection scope of the present invention.

Claims

1. A method for preparing all-solid waste autoclaved bricks using dry desulfurization ash, characterized in that: include: Using dry desulfurization ash as an activator, stirring it with fly ash, slag and water slag, and adding 11% to 15% of water during the stirring process to obtain a mixture; Pressing the mixture under a pressure of 10 to 15 MPa to obtain a brick; The brick blanks are cured in steam at 180° C. for 10 hours to obtain finished all-solid waste autoclaved bricks.

2. The method for preparing all-solid waste autoclaved bricks using dry desulfurization ash according to claim 1, characterized in that: The mass proportions of the components in the mixture are as follows: dry desulfurization ash: 10% to 30%, fly ash: 50% to 70%, slag: 10% to 25%, and water slag: 10% to 25%.

3. The method for preparing all-solid waste autoclaved bricks using dry desulfurization ash according to claim 1, characterized in that: The dry desulfurization ash is a fine powder solid waste discharged after a calcium-based desulfurizer absorbs SO2 in flue gas in a dry desulfurization process, and has a specific surface area of ​​10 to 30 m2 / g.

4. The method for preparing all-solid waste autoclaved bricks using dry desulfurization ash according to claim 1, characterized in that: The mass proportions of the components in the dry desulfurization ash are: Ca(OH)2: 20% to 65%, CaSO4: 20% to 40%, and CaCO3: 10% to 25%.

5. The method for preparing all-solid waste autoclaved bricks using dry desulfurization ash according to claim 1, characterized in that: The mass proportions of the main oxide components of the fly ash are: SiO2: 45% to 60%, Al2O3: 20% to 35%, Fe2O3: 5% to 10%, and CaO: 1% to 5%.

6. The method for preparing all-solid waste autoclaved bricks using dry desulfurization ash according to claim 1, characterized in that: The slag is a melt floating on the surface of liquid materials such as metals generated during the metallurgical process. The waste slag collected from the bottom of the boiler combustion chamber is granular after crushing. The slag particle size is 1mm to 3mm, and the bulk density is not more than 800kg / m 3 ; The slag contains SiO2, Al2O3, Fe2O3, CaO and a small amount of sulfide.

7. The method for preparing all-solid waste autoclaved bricks using dry desulfurization ash according to claim 1, characterized in that: The slag is solid waste discharged from the molten blast furnace slag produced by steel enterprises during iron smelting and rapidly cooled in water.

8. The method for preparing all-solid waste autoclaved bricks using dry desulfurization ash according to claim 1, characterized in that: The oxide components in the slag include: CaO, SiO2, Al2O3, MgO, CaS, MnS; the particle size of the slag is 1mm-10mm, and the bulk density is about 1350-1600kg / m 3 .

9. A fully solid waste autoclaved brick, characterized in that: The method is prepared by any one of claims 1 to 8.

10. The all-solid waste autoclaved brick according to claim 9, characterized in that: The mass percentage of each component is: dry desulfurization ash: 10% to 30%, fly ash: 50% to 70%, slag: 10% to 25%, and water slag: 10% to 25%.

Citation Information

Patent Citations

  • A semi-dry desulfurization ash autoclaved brick made from sintered flue gas and its production method

    CN103708808B